Pemahaman Peserta Didik di Kawasan Rawan Bencana Gempa Bumi Zona Menengah Di Kota Bengkulu - Fevi Wira Citra; Nurmintan Silaban; Dihamri Dihamri (Universitas Prof. Dr. Hazairin, S.H, 2022)
Bengkulu is located in an area prone to high earthquakes and an area prone to medium earthquakes. Medium earthquake-prone areas are areas that have the potential to be hit by earthquake shocks with an intensity ranging from VII MMI. The high level of earthquake intensity that occurred in Bengkulu caused the Bengkulu region to frequently experience earthquakes, so an action was needed in the form of socialization of disaster mitigation to increase public awareness. Mitigation related to public awareness actions is structural mitigation action, which is a form of mitigation action that is directly related to the level of public awareness, especially students, seen from the integrated disaster mitigation learning in the geography subject curriculum at the high school level. In the process of implementing disaster mitigation learning, students are required to understand what disasters often occur so that the introduction of earthquake disaster mitigation can be given and can be applied by students in a real action in dealing with disasters. The data used were questionnaires and questions distributed to Geography teachers and high school students in Bengkulu City. The level of understanding of mitigation in the middle zone of 138 students, the highest percentage achieved at the level of understanding is less with a percentage of 44% with a total of 60 students. The level of understanding of mitigation possessed by students in the middle zone with the highest percentage of 44% is in the condition of a low level of understanding. The average regression test of geography learning that occurs in Bengkulu City is 52.32% and understanding of mitigation in the intermediate zone is only 41.60%. In the middle zone, the level of understanding is at the level of understanding less with a percentage of 44% with the influence arising from understanding the mitigation that occurs in the research process is only 34.3% and the largest percentage at the level of understanding of mitigation that occurs by other factors in the form of environmental factors and environmental factors. information factor of 65.7%.